2020
DOI: 10.1111/imr.12913
|View full text |Cite
|
Sign up to set email alerts
|

γδ T cells and inflammatory skin diseases

Abstract: γδ and αβ T cells develop in the thymus from common progenitor cells. 1 Unlike αβ T cells, the majority of murine γδ T cells are functionally committed during intra-thymic differentiation. 2-4 This underlines the importance of the thymic microenvironment in the regulation of the peripheral effector functions of γδ T cells. Central to the thymic microenvironment is the thymic epithelial cells (TEC), divided into cortical TEC (cTEC) and medullary TEC (mTEC). 5 Particularly, the mTEC seem to regulate the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 176 publications
(285 reference statements)
0
22
0
Order By: Relevance
“…Because psoriasis alters the skin’s protective barrier, different microbes, irritants, and contact haptens/allergens more easily penetrate the cutaneous layer with presentation to dendritic cells. Therefore, allergic contact hypersensitivity has been reported as a possible comorbidity in psoriasis patients [ 1 , 2 , 3 , 13 ].…”
Section: Psoriasis and Allergic Contact Hypersensitivity As T-cell-me...mentioning
confidence: 99%
See 1 more Smart Citation
“…Because psoriasis alters the skin’s protective barrier, different microbes, irritants, and contact haptens/allergens more easily penetrate the cutaneous layer with presentation to dendritic cells. Therefore, allergic contact hypersensitivity has been reported as a possible comorbidity in psoriasis patients [ 1 , 2 , 3 , 13 ].…”
Section: Psoriasis and Allergic Contact Hypersensitivity As T-cell-me...mentioning
confidence: 99%
“…It affects all age groups, and its prevalence in the general population varies from 1% to 3%, with differences in various geographical areas due to environmental and genetic factors. Allergic contact dermatitis is caused by contact cell-mediated hypersensitivity and has a prevalence of about 15–20% in the general population [ 1 , 2 , 3 ]. This type IV hypersensitivity may be assessed in vivo with skin patch testing in selected patients with psoriasis and may be treated with either refractory or topical treatments, or with biologics if the patient is presenting with cutaneous lesions clinically suggestive of contact dermatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Among the adaptive effector cells, T cells play an essential role in the pathology of skin disorders by activating keratinocytes through the IL-23/IL-17 axis (11,12). Conventionally, TCRab + Th cells have received plentiful attentions, but increasing evidences have shown that IL-17-secreting TCRgd + (gd17) T cells are pivotal mediators in psoriasis (13)(14)(15). In both IL-23-induced and imiquimod (IMQ)-induced models, gd T cell deletion rather than ab T cell deletion alleviated skin inflammations (16).…”
Section: Introductionmentioning
confidence: 99%
“…These cells express T-cell receptors composed of γ and δ chains (γδTCRs), and their ligands are still unknown, as recently discussed [ 2 , 3 , 4 , 5 ]. γδT cells can mediate the human atopic state [ 6 , 7 , 8 ], and some researchers suggest that they are involved in the development of atopic dermatitis (AD) [ 9 , 10 , 11 , 12 ]. Because of the functional plasticity of γδT cells, which are typically divided into IL-17- and IFN-γ-producing γδT cells, γδT cells can also produce other cytokines with modulatory effects, such as IL-22 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%